Conceptos institucionales - Redondo, María Cristina (Revus (Ljubljana), 2019)
This paper proposes a reflection on a specific kind of legal concepts: those that delimit and allow to identify legal institutions. In the first part, three proposals, which are presented as competitive visions on this kind of institutional concepts, are taken into account. In the first place, Ronald Dworkin's interpretative-justifying conception, secondly, the reductionist conception associated with the realistic theory of Alf Ross. Finally, the criterial conception supported by a normativist legal positivism. In the second part of the work, these three proposals are put into play about a specific legal institution: the crime of witchcraft. The objectives of the paper are fundamentally two. On the one hand, to show that the analytical and metatheoretical approach of normativist legal positivism is not reducible to any of the other two and, in turn, relevant from a practical point of view. On the other hand, to show that the presentation of the considered proposals as if they were competitive approaches to institutional concepts is misleading. They don't talk about the same thing. They are guided by different methodological objectives and, above all, answer different questions concerning legal institutions.
Keywords: absolutism; cost-benefit analysis; čarovništvo; efficiency; institucije; institucionalni pojmi; interpretativni pojmi; kriterijski pojmi; negligence; precaution; priority of avoiding harm; responsibility; rights; risk; safety; trade-offs; utility; welfare; zmotna prepričanja